Macrophage-Derived Protein S Facilitates Apoptotic Polymorphonuclear Cell Clearance by Resolution Phase Macrophages and Supports Their Reprogramming - Lumbroso, Delphine; Soboh, Soaad; Maimon, Avi; Schif-Zuck, Sagie; Ariel, Amiram; Burstyn-Cohen, Tal (Frontiers in Immunology, 2018)
The complete resolution of inflammation requires the uptake of apoptotic polymorphonuclear cells by local macrophages (efferocytosis) and the consequent reprogramming of the engulfing phagocytes to reparative and pro-resolving phenotypes. The tyrosine kinase receptors TYRO3, AXL and MERTK (collectively named TAM) are fundamental mediators in regulating inflammatory responses and efferocytosis. Protein S (PROS1) is a ligand for all TAM receptors that mediates various aspects of their activity. However, the involvement of PROS1 in the resolution of inflammation is incompletely understood. Here, we report the upregulation of Pros1 in macrophages during the resolution of inflammation. Selective knockout of Pros1 in the myeloid lineage significantly downregulated macrophage pro-resolving properties. Hence, Pros1-deficient macrophages engulfed fewer apoptotic PMN remnants in vivo, and exogenous PROS1 rescued impaired efferocytosis ex vivo. Moreover, Pros1-deficient peritoneal macrophages secreted higher levels of the pro-inflammatory mediators TNFα, and CCL3, while they secreted lower levels of the reparative/anti-inflammatory IL-10 following exposure to LPS in comparison to their WT counterparts. Moreover, Pros1-deficient macrophages expressed less of the anti-inflammatory/pro-resolving enzymes arginase-1 and 12/15-lipoxygenase, and produced less of the specialized pro-resolving mediator resolvin D1. Altogether, our results suggest macrophage-derived PROS1 is an important effector molecule in regulating the efferocytosis, maturation and reprogramming of resolution phase macrophages, and imply PROS1 could provide a new therapeutic target for inflammatory and fibrotic disorders.